2021
DOI: 10.1029/2020jb021585
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variations of Slip and Creep Rates Along the Southern and Central Dead Sea Fault and the Carmel–Gilboa Fault System

Abstract: Crustal deformation and seismic activity in the Levant is mainly related to the interplate Dead Sea Fault (DSF) and the intraplate Carmel–Gilboa Fault System (CGFS). In this study, we analyze the interseismic deformation along these fault systems using 23 years of Global Positioning System (GPS) measurements obtained from 209 campaign and 60 continuous stations. This GPS data set is the longest record and the densest data set for the DSF, the CGFS, and the Levant region. We use this data set to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 66 publications
4
22
0
Order By: Relevance
“…Before 2013 and after 2018, the creep and slip rates are found to be similar, with a creep rate of 2.6 ± 0.3 mm/yr and a total slip rate of 4.0 ± 0.4 mm/yr, comparable to the results reported by Hamiel et al. (2016) and Hamiel and Piatibratova (2021). Between 2013 and 2018, our best‐fitting model indicates that the fault is locked, with a similar total slip rate of 4.0 ± 0.4 mm/yr to the total rate during the creeping periods.…”
Section: Gnss Data Analysis and Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Before 2013 and after 2018, the creep and slip rates are found to be similar, with a creep rate of 2.6 ± 0.3 mm/yr and a total slip rate of 4.0 ± 0.4 mm/yr, comparable to the results reported by Hamiel et al. (2016) and Hamiel and Piatibratova (2021). Between 2013 and 2018, our best‐fitting model indicates that the fault is locked, with a similar total slip rate of 4.0 ± 0.4 mm/yr to the total rate during the creeping periods.…”
Section: Gnss Data Analysis and Resultssupporting
confidence: 87%
“…The third explanation was recently discussed by Barnea Cohen et al (2022). This study followed the studies of Hamiel et al (2016) and Hamiel and Piatibratova (2021), which found that the northern Jordan Valley segment of the DSF is creeping at shallow depths, and suggested that the shallow creep induces shallow seismic activity beneath the northern part of the Sea of Galilee. Barnea Cohen et al ( 2022) used seismic data and showed that the earthquake distribution and focal mechanism suggest shallow NW-SE normal faults splaying from the tip of the creeping segment.…”
Section: 1029/2022gl100584mentioning
confidence: 60%
See 2 more Smart Citations
“…After presenting the proposal, we test the hypothesis and finally discuss previous mechanisms that have been proposed. Recent geodetic measurements across the Jordan Valley Fault, on a southern tangent of Lake Kinneret, indicate lateral creep of 2.5 ± 0.8 mm/year from the surface down to a depth of 1.5 ± 1.0 km, over a approximately 40 km distance (Hamiel et al., 2016; Hamiel & Piatibratova, 2021). A factor promoting slow slip could be a buried salt layer, as suggested for the Jordan Valley Fault by Hamiel et al.…”
Section: Discussionmentioning
confidence: 99%